Serous Cystic Neoplasms of the Pancreas: Endoscopic Ultrasonographic Versus Computed Tomography and Magnetic Resonance Imaging Features of Surgically Removed Masses. Issue 3 (September 2018) - Hwang, Hyeonseung; Yu, Jeong-Sik; Cho, Eun-Suk; Kim, Joo Hee; Chung, Jae-Joon
Abstract : Abstract: Our purpose was to assess the endoscopic ultrasonography (EUS) features of serous cystic neoplasms (SCNs) of the pancreas in determining the surgical removal compared with computed tomography (CT) and magnetic resonance imaging (MRI) features. For 33 consecutive patients with 34 surgically confirmed SCNs over the past 11 years, preoperative EUS features were compared with those of CT and MRI (CT&MRI). Besides the lesion size and location, a retrospective analysis of the various imaging features was performed by 2 observers to understand the characteristics that determine the need for surgical intervention in terms of multiplicity of locules, calcification, mural thickening, mural nodules, ductal communication, and main pancreatic duct dilatation in addition to the gross morphologic type: microcystic, macrocystic (>1 cm), mixed, or solid. The most common gross morphologic type was mixed lesions, which consisted of microcystic and macrocystic components (15/34; 44%), followed by microcystic (38%), macrocystic (15%), and solid (3%) lesions. A minority (5/34; 18%) of the lesions showed main pancreatic duct dilatation (upstream, n = 3; downstream, n = 0; diffuse, n = 2). Mural nodules or solid components were more frequently noted in EUS (67%) than in CT&MRI (25%; P = 0.001), whereas other findings showed no remarkable difference between EUS and CT&MRI ( P > 0.05). In determining the surgical treatment of multiloculated cystic lesions, interpretation of EUS features for the presence of solid component or mural nodules should be more carefully determined, especially in the patients with suggestive features of SCN on CT or MRI to avoid unnecessary surgery.